Epigenetics in T‐cell acute lymphoblastic leukemia. Issue 1 (January 2015) - Peirs, Sofie; Van der Meulen, Joni; Van de Walle, Inge; Taghon, Tom; Speleman, Frank; Poppe, Bruce; Van Vlierberghe, Pieter
Summary: Normal T‐cell development is a strictly regulated process in which hematopoietic progenitor cells migrate from the bone marrow to the thymus and differentiate from early T‐cell progenitors toward mature and functional T cells. During this maturation process, cooperation between a variety of oncogenes and tumor suppressors can drive immature thymocytes into uncontrolled clonal expansion and cause T‐cell acute lymphoblastic leukemia (T‐ALL). Despite improved insights in T‐ALL disease biology and comprehensive characterization of its genetic landscape, clinical care remained largely similar over the past decades and still consists of high‐dose multi‐agent chemotherapy potentially followed by hematopoietic stem cell transplantation. Even with such aggressive treatment regimens, which are often associated with considerable side effects, clinical outcome is still extremely poor in a significant subset of T‐ALL patients as a result of therapy resistance or hematological relapses. Recent genetic studies have identified recurrent somatic alterations in genes involved in DNA methylation and post‐translational histone modifications in T‐ALL, suggesting that epigenetic homeostasis is critically required in restraining tumor development in the T‐cell lineage. In this review, we provide an overview of the epigenetic regulators that could be implicated in T‐ALL disease biology and speculate how the epigenetic landscape of T‐ALL could trigger the development of epigenetic‐based therapies to further improve the treatment of human T‐ALL.